It's All About MeE: Using Structured Experiential Learning (“e”) to Crawl the Design Space - and Pritchett, Lant; Samji, Salimah; Hammer, Jeffrey (Center for Global Development, 2013)
This paper argues that within-project variations in design can serve as their own counterfactual, reducing the incremental cost of evaluation and increasing the direct usefulness of evaluation to implementing agencies. It suggests combining monitoring (‘M’), structured experiential learning (‘e’), and evaluation (‘E’) so as to facilitate innovation and organisational capability building while also providing accountability …